Reduced Graphene Oxide Electrodes with Wrinkled Surface for Nonvolatile Polymer Memory Device Compatibility. Issue 7 (26th April 2018) - Chen, Jie; Wang, Xiangjing; Lu, Hang; Liu, Zhengdong; Xiu, Fei; Ban, Chaoyi; Zhou, Zhe; Song, Mengya; Ju, Shang; Chang, Qing; Liu, Juqing; Huang, Wei
Abstract: A general strategy for high performance nonvolatile polymer memory devices, with wrinkled reduced graphene oxide (rGO) films as electrodes and common insulating polymers as active layers, is proposed. The fabricated device exhibits electrical bistability and nonvolatile write‐once‐read‐many times‐type memory, with a low switching voltage of 2.7 V, high ON/OFF ratio of 10 4 and desirable long retention time over 10 4 s. The resistive switching of the device might be attributed to carbon‐rich filaments induced by the wrinkled rGO surface. Moreover, this polymer memory device based on a wrinkled rGO electrode can be further applied to flexible data storage systems. The strategy combining such advances in polymer memory devices with simple structure, common materials, excellent reproducibility, and high performance will demonstrate great potential in permanent archival storage applications. Abstract : A general strategy for high‐performance, nonvolatile polymer memory devices, with wrinkled reduced graphene oxide films as the electrodes and common insulating polymers as the active layers, is proposed. The fabricated device exhibits nonvolatile write‐once‐read‐many times‐type memory, with a low switching voltage, high ON/OFF ratio, long retention time, and excellent reproducibility and flexibility, thus demonstrating great potential for permanent archival storage applications.